Understanding burn injuries in children—A step toward prevention and prompt first aid. Issue 4 (June 2022) - D'cunha, Aureen; Rebekah, Grace; Mathai, John; Jehangir, Susan
Highlights: Awareness of first aide in burns is improving in India. The application of this knowledge however is still lacking. Health care personnel can contribute more to reinforce correct attitudes. Safety standards in the home are still wanting. Abstract: This study was designed to examine knowledge, attitude and practices with regards to burns prevention and first aid in the Indian community. A total of 83 caregivers aged 19 and 40 years (mean 29 years) participated in survey. Sixty-one percent of those who responded to the survey had some knowledge of first aid, mostly through health education at schools (59%). Very few (2%) received first aid education from health workers. Approximately 2/3 of responders (66–70%) were aware of applying cool running water to a burn and to stop drop and roll in case of a flame burn. However, the same number also listed a myriad of household remedies that they would use as first aid. 66–71% responders were aware of some situational risks in the home and community but only 27% considered young children to be at greater risk. 31% responders had an enclosed kitchen and 16% were still cooking on the floor. A large percentage (83%) cooked outside on a traditional wooden open fire. A quarter of the responders still used oil lamps on the floor and had little regard for the flammability of clothes. There was a weak positive correlation between knowledge and attitude (r-square 0.379) and attitude and practice (r-square 0.373), but no correlation between knowledge and practice (r-square 0.089). Our survey suggests that many responders have limited knowledge of effective first-aid techniques and live in high-risk environments. The major sources of first aid information were from school-based health education, social and electronic media. These resources can be utilized to further disseminate knowledge on first aid and practical prevention techniques.